Heat Transfer Analysis of Continuous and Staggered Fin Arrays - Kumbhar, S. V.; Jadhav, A. R.; Jadhav, M. A.; Bardiya, S. G. (Asian Review of Mechanical Engineering, 2018)
There are many ways to transfer heat from one medium to another medium efficiently. Heat dissipation is an important issue to tackle due to compacting of equipment and miniaturization. Heat exchangers are not only chosen for their thermal better performance but also for their other design parameters such as weight, cost, ease of handling etc. This paper briefly focuses on the study of continuous and staggered fin arrays.